PENGUKURAN TINGKAT KEPUASAN WISATAWAN TERHADAP PELAYANAN DIVE SHOP AQURA DIVE - Roseven Rudiyanto (JURNAL AKADEMISI VOKASI, 2023)
Tourism is an industry that offers experiences to tourists. Therefore, service quality is essential in the tourism industry. One of the developing destinations in Indonesia is Labuan Bajo. The indicator of tourism industry development in Labuan Bajo is various tourism services. Acura Dive is one of the dive shops in Labuan Bajo. It is located on Seraya Kecil Island and has become part of the Sudamala Seraya Resort. Therefore, this research aims to determine tourist satisfaction with Aquara Dive services. This study uses a quantitative approach. The method to define the level of tourist satisfaction in three steps, namely 1) obtaining the ideal score by multiplying the number of respondents by the very satisfied score, namely 5, 2) divide the item score obtained by the total ideal score to get the level of satisfaction and, 3) interpreting the level of satisfaction. The interpretation of satisfaction levels is as follows. 0% - 20% = Very Dissatisfied, 21% - 40% = Dissatisfied, 41% - 60% = Somewhat Satisfied, 61% -80% = Satisfied, and 81% - 100% = Very Satisfied. The number of respondents reached 172 people. Based on data analysis, the satisfaction level of users of the Acura Dive service is 97%, and it is in the category very satisfied.